2014
DOI: 10.1007/s00586-014-3264-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of cervical spondylotic myelopathy

Abstract: In this narrative review, we aim to outline what is currently known about the pathophysiology of cervical spondylotic myelopathy (CSM), the most common cause of spinal cord dysfunction. In particular, we note the unique factors that distinguish it from acute spinal cord injury. Despite its common occurrence, the reasons why some patients develop severe symptomatology while others have few or no symptoms despite radiographic evidence confirming similar degrees of compression is poorly understood. Neither is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 44 publications
1
148
1
1
Order By: Relevance
“…In summary, neurodegeneration in CSM, although different in causation, disease onset and progression trajectory, 3 resembles the pathophysiological processes of antero-and retrograde degeneration observed after spinal cord injury. 38,46,47 …”
Section: Journal Of Neurotraumamentioning
confidence: 74%
See 2 more Smart Citations
“…In summary, neurodegeneration in CSM, although different in causation, disease onset and progression trajectory, 3 resembles the pathophysiological processes of antero-and retrograde degeneration observed after spinal cord injury. 38,46,47 …”
Section: Journal Of Neurotraumamentioning
confidence: 74%
“…Propriospinal circuitries 35,36 and corticospinal projections to motor neurons 37 might be indirectly perturbed by the stenosis leading to remote neurodegeneration (e.g. axonal degeneration, neuronal loss) 3,38 which cause the mean diffusivity to increase. On the contrary, in the dorsal horns, prominent atrophy in the absence of diffusivity changes was evident above the compression site.…”
Section: Insights Into Spinal Cord Grey Matter Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…From the long-term observation of 3D images, we found that the vascular density of compression group had no significant different compared with that of the sham group at the 70th day. A few of studies showed that compensatory mechanisms and angiogenesis might exist in chronic compressive spinal cord injury [17,22]. These mechanisms could be useful to explain the alteration of integral vascular network at different time after spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spondylotic myelopathy(CSM) is a progressive degenerative disease that results in compression of the cervical spinal cord or nerve roots, leading to neurologic dysfunction[1-3]. It is the leading cause of progressive disability and represents a major public health importance as its prevalence increases in an aging population[4-6].…”
Section: Introductionmentioning
confidence: 99%